Patient-derived primary breast cancer cells and their potential for predicting sensitivity to chemotherapy - Mou, Yajun; Huang, Jianjun; Yang, Wenxiu; Wan, Yu; Pu, Zhenhong; Zhang, Junhong; Liu, Jinting; Li, Qing; Zhang, Peipei; Tian, Yuan; Yang, Hui; Cui, Yi; et al. (Frontiers in Oncology, 2022)
Chemotherapy resistance exposes patients to side effect and delays the patients of effect therapy. As far, there are no precision predictive tools to predict resistancer to chemotherapy and then select the sensitive chemotherapeutic drugs to the patient. Here, we aim to develop an in vitro primary cells culture model from the breast cancer patients living cells for predicting the sensitivity to chemotherapy. We created primary breast cancer cell medium BCMI and culture system with higher efficiency of model establishment. Immunofluorescence staining of ERα, PR and HER2 confirmed the identification of the breast cancer patient biopsies and resections. Killing assay showed that these primary breast cancer cells responded variously to Doxorubicin or Pirarubicin treatment. This platform of primary breast cancer cell culture hold great promise to predict chemotherapeutic drugs sensitivity for the personalized breast cancer patient.